2009
DOI: 10.1063/1.3269605
|View full text |Cite
|
Sign up to set email alerts
|

Improving microstructural quality of semipolar (112̱2) GaN on m-plane sapphire by a two-step growth process

Abstract: This letter reports a two-step growth process for improving microstructural quality of semipolar (112̱2) GaN on nitridized m-plane sapphire. The two-step growth of (112̱2) GaN, islanding growth under high pressure followed by islands coalescence under low pressure, went through a roughening-recovery process, which was found very effective in reducing the density of stacking faults and dislocations in (112̱2) GaN. The x-ray rocking curves of both on-axis and off-axis planes were narrowed down by more than 50%. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
113
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(117 citation statements)
references
References 17 publications
4
113
0
Order By: Relevance
“…19 Reports on the structural anisotropy of semipolar GaN just begun to emerge and the on-axis RC of semipolar ͑1122͒ GaN films have been recently found to also exhibit anisotropic behavior. 20 The structural anisotropy of nonpolar III-nitride films affects their optical performance and device-relevant characteristics ͑carrier mobility, degradation, etc.͒, which requires detailed study of these issues. While the structural anisotropy of nonpolar GaN films have been extensively studied 1, [14][15][16][17][21][22][23] the information on the structural characteristics of nonpolar InN is very scarce 24,25 and detailed reports exists only for films grown on GaN substrates.…”
Section: Introductionmentioning
confidence: 99%
“…19 Reports on the structural anisotropy of semipolar GaN just begun to emerge and the on-axis RC of semipolar ͑1122͒ GaN films have been recently found to also exhibit anisotropic behavior. 20 The structural anisotropy of nonpolar III-nitride films affects their optical performance and device-relevant characteristics ͑carrier mobility, degradation, etc.͒, which requires detailed study of these issues. While the structural anisotropy of nonpolar GaN films have been extensively studied 1, [14][15][16][17][21][22][23] the information on the structural characteristics of nonpolar InN is very scarce 24,25 and detailed reports exists only for films grown on GaN substrates.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, employing shorter microrods is useful for removing additional BSFs, leading to further improvement in crystal quality. The results presented provide a very promising approach to eventually achieving (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) Semi-polar GaN, particularly in the (11-22) orientation, has emerged to be a promising candidate for fabricating both light emitting diodes (LEDs) and laser diodes (LDs) with a long wavelength beyond the blue spectral region, e.g., green and yellow, which is critical for solid state lighting, visible light communications and opto-genetics. The current status of the development of (11-22) GaN on sapphire can be referred to a topical review published very recently.…”
mentioning
confidence: 99%
“…This can be achieved by carefully designing micro-rod templates. Based on transmission electron microscopy and photoluminescence measurements, it has been found that the micro-rod diameter plays a vital role in effectively reducing both the dislocation density and the basal staking fault (BSF) density of the overgrown (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) GaN, but in different manners. The BSF density reduces monotonically with increasing the micro-rod diameter from 2 to 5 lm, and then starts to be saturated when the micro-rod diameter further increases.…”
mentioning
confidence: 99%
See 2 more Smart Citations